Short-term Pilates protocol promotes improvement in the functional performance of juvenile soccer players (Research, Society and Development, 2022)
The objective of the study was to investigate the effects of a training program with the Pilates Method on muscle fatigue in youth soccer players. Fifteen male soccer players, sub 13-15 category, with a mean age of 13.27 ± 0.45 years, were randomly divided into two groups: Control group (n = 7) and Pilates group (n = 8). In the Pilates group, an additional training protocol was performed with the Pilates Method alone. In both groups, the concentration of cytokines (TNFα, IL-10), the electrical activity of the rectus femoris, rectus abdominis, biceps femoris and gluteus maximus muscles was evaluated and the Side Hop Test was performed. In both groups, there were no significant changes in the cytokine profile and in the electrical activity of the evaluated muscles, but there was a significant difference in the time taken to perform the Side Hop test for the Pilates group. The application of the Pilates method (solo) as an additional training in youth soccer players did not show greater tolerance to muscle fatigue, however it may have generated an improvement in the functional performance of the athletes.